Companies taxation in Nigeria : including petroleum profits tax - Ariwodọla, J. A. (Lagos : JAA Nigeria Limited, 1988)
The book covers the laws and practice relating to companies taxation in Nigeria including petroleum profit tax and is a companion volume to the author's book on personal taxation
Includes index.
osc 28/01/2019, ijb 27/03/2019
Loans
Keywords: Corporations; Petroleum; Excess profits tax